Prevalence of Cardiovascular Autonomic Neuropathy among Patients with End Stage Renal Disease (ESRD) On Hemodialysis in King Khalid Hospital, Najran (KKH-N) - Al-Abataheen N.M., Almakramy A.H., Mokhtar I.; Abdelmajed A.H., Elhussien E.A., Nanaa A.A., Abdulla F.I. (International Journal of Innovative Research in Medical Science, 2017)
Autonomic dysfunction is a common and potentially life-threatening complication of chronic kidney disease (CKD), and can occur in the absence of length-dependent uremic neuropathy. It may affect various body systems including cardiovascular, gastrointestinal, genitourinary and other body systems leading to significant morbidity. Cardiovascular autonomic dysfunction in CKD is associated with an increased risk of cardiac arrhythmia and sudden cardiac death. In addition to a potential role in sudden cardiac death, reduced bar reflex sensitivity can also contribute to intradialytic hypotension, a condition occurring during dialysis that is characterized by an abrupt reduction in blood pressure without a compensatory increase in heart rate. Beside comprehensive history and physical examination, Ewing’s five standard cardiovascular reflex tests were used for the assessment of autonomic function. After analysis the result, the majority of patients with ESRD on Hemodialysis has evidence of cardiovascular autonomic dysfunction. Significantly more patients has evidence of cardiovascular sympathetic dysfunction (82 %) than patients with evidence of cardiovascular parasympathetic dysfunction (56 %) (P < 0.05). Further work is needed to determine risk factors for development of autonomic dysfunction and measures to reduce it in this patient group.